2023
DOI: 10.3390/nu15214681
|View full text |Cite
|
Sign up to set email alerts
|

Diet’s Impact on Post-Traumatic Brain Injury Depression: Exploring Neurodegeneration, Chronic Blood–Brain Barrier Destruction, and Glutamate Neurotoxicity Mechanisms

Matthew Boyko,
Benjamin F. Gruenbaum,
Anna Oleshko
et al.

Abstract: Traumatic brain injury (TBI) has a profound impact on cognitive and mental functioning, leading to lifelong impairment and significantly diminishing the quality of life for affected individuals. A healthy blood–brain barrier (BBB) plays a crucial role in guarding the brain against elevated levels of blood glutamate, making its permeability a vital aspect of glutamate regulation within the brain. Studies have shown the efficacy of reducing excess glutamate in the brain as a treatment for post-TBI depression, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 181 publications
0
2
0
Order By: Relevance
“…Several factors can disrupt and cause the normally stable levels of blood glutamate concentrations to fluctuate. One of these factors may be dietary intake, caused by the presence of glutamate in many foods [ 33 ]. Traditional diets in Asian countries include high levels of glutamate because monosodium glutamate (MSG) is a popular flavoring in many cuisines, especially in East and Southeast Asian cuisine [ 103 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors can disrupt and cause the normally stable levels of blood glutamate concentrations to fluctuate. One of these factors may be dietary intake, caused by the presence of glutamate in many foods [ 33 ]. Traditional diets in Asian countries include high levels of glutamate because monosodium glutamate (MSG) is a popular flavoring in many cuisines, especially in East and Southeast Asian cuisine [ 103 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent related hypothesis points to the development of post-TBI neuropsychiatric sequelae through chronic blood–brain barrier (BBB) destruction, chronic glutamate neurotoxicity, and neurodegeneration [ 31 , 32 ]. In a previous investigation, we examined the effect of dietary glutamate on chronic neurotoxicity and its role in the development of post-TBI depression [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances in glutamatergic signaling have been associated with the pathogenesis of, among others, such mental disorders as schizophrenia, bipolar disorder, anxiety and depression [63]. Plasma glutamate concentration is associated with the severity of depression [64]. Luykx et al in their metaanalysis, draw attention to brain region-specific changes in depression that are dependent on glutamate level [65].…”
Section: Correlation Analysis Of Lactates Glutamic Acid and Cortisol ...mentioning
confidence: 99%
“…Depression is one of the most common psychiatric sequelae ensuing from TBI, it might influence 25–50% of TBI patients (Jahan & Tanev, 2023 ). Studies suggested that TBI-related depression significantly affected personal life quality and even resulted in lifelong impairment (Boyko et al, 2023 ). Nevertheless, much remains unclear about the complicated neurobiological alternations of post-TBI depression.…”
Section: Introductionmentioning
confidence: 99%